2022
DOI: 10.1111/jcmm.17530
|View full text |Cite
|
Sign up to set email alerts
|

Larotrectinib induces autophagic cell death through AMPK/mTOR signalling in colon cancer

Abstract: Larotrectinib (Lar) is a highly selective and potent small-molecule inhibitor used in patients with tropomyosin receptor kinase (TRK) fusion-positive cancers, including colon cancer. However, the underlying molecular mechanisms specifically in patients with colon cancer have not yet been explored. Our data showed that Lar significantly suppressed proliferation and migration of colon cancer cells. In addition, Lar suppressed the epithelial-mesenchymal transition (EMT) process, as evidenced by elevation in E-cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although various anticancer drugs have been developed to treat lung cancer, new therapies are needed due to their many side effects. Recently, many studies have investigated anticancer effects through autophagy activity [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Although various anticancer drugs have been developed to treat lung cancer, new therapies are needed due to their many side effects. Recently, many studies have investigated anticancer effects through autophagy activity [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a process that regulates cancer survival during stress ( 52 ). Several studies have suggested that autophagy induction inhibits tumor initiation and progression ( 53 , 54 ). Therefore, whether the inhibitory effect of MSpf treatment on cell proliferation was due to induction of autophagy was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that MTOR signaling dependent mitochondrial dysfunction promotes colorectal cancer cell death[ 77 ]. Regulation of the Beclin1/Beclin2 signaling pathway may be the key to inducing autophagic death of colorectal cancer cells[ 78 - 80 ]. In addition, a study on the mechanism of lipopolysaccharide-induced injury in the colon adenoma cell lines Caco-2 and HT-29 showed that autophagic flow was blocked at the autolysosome stage in vitro and in vivo [ 81 ].…”
Section: Autophagy and Gi Diseasesmentioning
confidence: 99%